Sequential processing deficit as a shared persisting biomarker in dyslexia and childhood apraxia of speech. (3rd April 2018) - Peter, Beate; Lancaster, Hope; Vose, Caitlin; Middleton, Kyle; Stoel-Gammon, Carol
ABSTRACT: The purpose of this study was to investigate the hypothesis that individuals with dyslexia and individuals with childhood apraxia of speech share an underlying persisting deficit in processing sequential information. Levels of impairment (sensory encoding, memory, retrieval, and motor planning/programming) were also investigated. Participants were 22 adults with dyslexia, 10 adults with a probable history of childhood apraxia of speech (phCAS), and 22 typical controls. All participants completed nonword repetition, multisyllabic real word repetition, and nonword decoding tasks. Using phonological process analysis, errors were classified as sequence or substitution errors. Adults with dyslexia and adults with phCAS showed evidence of persisting nonword repetition deficits. In all three tasks, the adults in the two disorder groups produced more errors of both classes than the controls, but disproportionally more sequencing than substitution errors during the nonword repetition task. During the real word repetition task, the phCAS produced the most sequencing errors, whereas during the nonword decoding task, the dyslexia group produced the most sequencing errors. Performance during multisyllabic motor speech tasks, relative to monosyllabic conditions, was correlated with the sequencing error component during nonword repetition. The results provide evidence for a shared persisting sequential processing deficit in the dyslexia and phCAS groups during linguistic and motor speech tasks. Evidence for impairments in sensory encoding, short-term memory, and motor planning/programming was found in both disorder groups. Future studies should investigate clinical applications regarding preventative and targeted interventions towards cross-modal treatment effects.